New Education Models for the Future of Work Force - Francesco Pastore (Global Labor Organization (GLO), 2018)
This paper addresses the directions to follow when designing new educational systems and school-to-work transition regimes to adhere to the needs of Industry 4.0. Although a high level of general education will be important for its training content to develop adaptability, it is not the only component to develop. What will be more and more important are work related skills, both the general ones and the ones which are job-specific and need, therefore, on-the-job training to develop. This will require important educational reforms to favour an ever-better integration between educational institution and the world of work. Young people and their families alone will not be able to adapt on their own to the new human capital requirements of industry 4.0 productions. A new framework for an integrated action by governments, firms, educational institutions and families is needed to smooth the school-to-work in the future. The duality principle is the basis for a strong diversification of the supply of education.
Keywords: J24; L16; O15; O33; Q2; Q55; 330; industry 4.0; robotics; sequential versus dual education systems; human resources management and policy